Pronounced Virus-dependent Activation Drives Exhaustion but Sustains Interferon-γ Transcript Levels - Mackerness, Kathryn J. (2010)
During many chronic infections the responding CD8 T cells become exhausted as they progressively lose their ability to elaborate key effector functions. Unlike prototypic memory CD8 cells, which rapidly synthesize IFN-γ following activation, severely exhausted T cells fail to produce this effector molecule. Nevertheless, the ontogeny of exhausted CD8 T cells as well as the underlying mechanisms that account for their functional inactivation remains ill-defined. We have utilized cytokine reporter mice, which mark the transcription of IFN-γ mRNA by the expression of Thy1.1, to decipher how activation events during the early stages of a chronic infection dictate the development of exhaustion. We show that virus-specific CD8 T cells clearly respond during the early stages of chronic lymphocytic choriomeningitis virus (LCMV) infection, and that this early T cell response is more pronounced than that initially observed in acutely infected hosts. Thus, exhausted CD8 T cells appear to emerge from populations of potently activated precursors. Unlike acute infections, which result in massive expansion of the responding T cells, there is a rapid attenuation of further expansion during chronic infections. The exhausted T cells that subsequently emerge in chronically infected hosts are incapable of producing the IFN-γ protein. Surprisingly, high levels of the IFN-γ transcript are still present in exhausted cells, demonstrating that ablation of IFN-γ production by exhausted cells is not due to transcriptional silencing. Thus, post-transcription regulatory mechanisms likely disable this effector module.